2020
DOI: 10.3390/jcm9041068
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Alcohol Hangover on Mood and Performance Assessed at Home

Abstract: The current study evaluated the next day consequences of a social night of drinking compared to a no alcohol night, with standardised mood and portable screen-based performance measures assessed in the morning at participants’ homes, and a breathalyser screen for zero alcohol. A mixed sex group (n = 20) took part in the study. Participants reported consuming on average 16.9 units (135 g) alcohol, resulting in a hangover rating of 60 (out of 100) compared to 0.3 following the no alcohol night. Statistical signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 57 publications
3
13
2
Order By: Relevance
“…Given previous links between mental health, mood, and alcohol ( Birnbaum et al, 1983 ; Parker et al, 1987 ; Howland et al, 2010 ; Alford et al, 2020 ), it was predicted that those who were drinking more during lockdown would have higher negative mood scores. This prediction was not borne out in the analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given previous links between mental health, mood, and alcohol ( Birnbaum et al, 1983 ; Parker et al, 1987 ; Howland et al, 2010 ; Alford et al, 2020 ), it was predicted that those who were drinking more during lockdown would have higher negative mood scores. This prediction was not borne out in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst there is evidence to suggest that alcohol-dependant individuals drink to alleviate negative emotional states ( Koob, 2011 ), the relationship between emotional experience and alcohol in social drinkers is less-clearly defined ( Sayette, 2017 ). Poor mental health has consistently been reported in abusive ( Pottenger et al, 1978 ; Grant and Harford, 1995 ; Schuckit, 2006 ) and social drinkers ( Birnbaum et al, 1983 ; Parker et al, 1987 ; Jones et al, 2007 ), and drinking alcohol has been associated with negative mood ( Howland et al, 2010 ; Alford et al, 2020 ). In our study we focused specifically on changes to drinking behavior and examined links between these changes, socio-demographic and COVID-induced change circumstances, and negative mood.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, there are presumably other reasons than mere degree of intoxication that determine whether participants discontinue study participation or not. A different approach has been the use of mobile technology, including screen-based tests, to enable participants to be assessed within the privacy and safety of their own homes, without the need to travel to the test center when hungover, avoiding dropouts [32].…”
Section: Implications For Hangover Researchmentioning
confidence: 99%
“…Additionally, the mechanisms by which anger can influence alcohol use have not been fully elucidated. Following heavy alcohol use, negative mood states, including irritability, are common (Alford, Martinkova, Tiplady, Reece, and Verster, 2020). It has been suggested that, even among individuals without alcohol use disorder, individuals learn to recognize early interoceptive cues of oncoming negative affect as alcohol is eliminated from the body, often preconsciously.…”
mentioning
confidence: 99%